Hgs (Hrs), a FYVE Domain Protein, Is Involved in Smad Signaling through Cooperation with SARA - Shigeto Miura; Toshikazu Takeshita; Hironobu Asao; Yutaka Kimura; Kazuko Murata; Yoshiteru Sasaki; Jun‐ichi Hanai; Hideyuki Beppu; Tomoo Tsukazaki; Jeffrey L. Wrana; Kohei Miyazono; Kazuo Sugamura (2000)
Smad proteins are effector molecules that transmit signals from the receptors for the transforming growth factor beta (TGF-beta) superfamily to the nucleus; of the Smad proteins, Smad2 and Smad4 are essential components for mouse early embryogenesis. We demonstrated that Hgs, a FYVE domain protein, binds to Smad2 in its C-terminal half and cooperates with another FYVE domain protein, the Smad anchor for receptor activation (SARA), to stimulate activin receptor-mediated signaling through efficient recruitment of Smad2 to the receptor. Furthermore, a LacZ knock-in allele of the C-terminal half-deletion mutant of mouse Hgs was created by gene targeting. The introduced mutation causes an embryonic lethality between embryonic days 8.5 and 10.5. Mutant cells showed significantly decreased responses to stimulation with activin and TGF-beta. These findings suggest that the two FYVE domain proteins, Hgs and SARA, are prerequisites for receptor-mediated activation of Smad2.